A novel MRI‐based three‐dimensional model of stomach volume, surface area, and geometry in response to gastric filling and emptying. Issue 2 (23rd November 2022) - Bertoli, Davide; Mark, Esben Bolvig; Liao, Donghua; Brock, Christina; Frøkjær, Jens Brøndum; Drewes, Asbjørn Mohr
Abstract: Background: Gastric motility and accommodation have a critical role in maintaining normal gastrointestinal homeostasis. Different modalities can be adopted to quantify those processes, that is, scintigraphy to measure emptying time and intragastric Barostat for accommodation assessment. However, magnetic resonance imaging (MRI) can assess the same parameters noninvasively without ionizing radiation. Our study aimed to develop a detailed three‐dimensional (3D) MRI model of the stomach to describe gastric volumes, surface areas, wall tension distribution, and interobserver agreement. Methods: Twelve healthy volunteers underwent an MRI protocol of six axial T2‐weighted acquisitions. Each dataset was used to construct a 3D model of the stomach: First, the volumes of the whole stomach, gastric liquid, and air were segmented. After landmark placing, a raw 3D model was generated from segmentation data. Subsequently, irregularities were removed, and the model was divided into compartments. Finally, surface area and 3D geometry parameters (inverse curvatures) were extracted. The inverse curvatures were used as a proxy for wall tension distribution without measuring the intragastric pressure. Key Results: The model was able to describe changes in volume and surface geometry for each compartment with a distinct pattern in response to filling and emptying. The surface tension was distributed nonhomogeneously between compartments and showed dynamical changes at various time points. Conclusion & Inferences: The presented model offers a detailed tool for evaluating gastric volumes, surface geometry, and wall tension in response to filling and emptying and will provide insights into gastric emptying and accommodation in diseases such as diabetic gastroparesis. Abstract : This study presents a three‐dimensional stomach model able to report volume and surface data and describe the distribution of the gastric wall tension, volume, and surface. The method was able to provide insights into both gastric emptying and accommodation in different gastric compartments.